An Efficient IoT Based Smart Irrigation System and Plant Diseases Detection: A Review - NagaGeetha, M; N.V.K Ramesh, Dr (International Journal of Engineering and Technology, 2018)
The irrigation control and monitoring of the involved variables on the plant growth are actions that farmers must implement in their crops to save water resources and assessing the growth of the plant. In this paper, the literature is conducted on several authors’ works, their modern way of doing agriculture with IoT and image processing combination, thus the paper gives information about various techniques, algorithms, and architectures employed to detect the crop diseases in advance so that proper care can be taken to avoid it. Hence incorporating IoT with image processing gives improved detection ability in the agricultural system. The survey comprises several authors’ workouts of automated Irrigation and crop diseases Detection practices which are currently in use..
Keywords: Disease Diagnosis; Internet of Things (IoT); MATLAB; Image Processing; Sensing network.